التحول الرقمي ودوره في تشكيل هوية المرأة الاكاديمية بالجامعات الليبية: دراسة ميدانية (Journal of Academic Research, 2026)
Digital transformation and its role in shaping the academic identity of women in Libyan Universities (Field study) Abstract:     This study aims to identify the role of digital transformation in shaping the identity of female academics in Libyan universities. To achieve this, the study adopted a descriptive approach due to its suitability for the nature and objectives of the current study. An electronic questionnaire was designed and distributed to a random sample of female academics at Libyan universities, totaling (150) female academics. To answer the study's questions, arithmetic means, standard deviations, and scores were extracted. The study concluded with a number of findings, the most: important of which were that digital transformation had a positive role in shaping the identity of female academics in Libyan universities, that the level of female academics' engagement was high on              the platforms (WhatsApp, Facebook, Telegram, YouTube) respectively, the most important cultural elements in the adherence of female academics were Islamic law (religion), while at the same time the digital transformation had a moderate positive impact on the identity of female academics, and had no negative impact on the formation of women academics' identity. The repercussions of the digital transformation on the formation of women academics' identity in Libyan universities in terms of education, professional, cultural, health, social, and political aspects were positive.                         Keywords: Digital transformation, women's identity, female academics, Libyan universities.